A fully integrated buck converter with a novel digital soft-start circuit. Issue 2 (2nd April 2016) - Zhang, Zhang; Song, Mingxin; Wang, Xing; Cheng, Zhengxi; Xie, Guangjun
Abstract: A novel digital soft-start circuit in the fully integrated buck converter is presented in this paper. The soft-start approach based on a linearly ramped-up reference is proposed to prevent massive in-rush current and overshoot voltage during the start-up phase of the buck converter. Compared with conventional soft-start circuit, the novel circuit is realized by a compact on-chip circuit that requires no external pins and is very simple as well. A fully integrated DC–DC buck converter with proposed circuit has been based on a 0.18 μm mixed signal CMOS process. The results show that this novel soft-start enables the output voltage of the converter to be linearly ramped up to the steady state.